2008
DOI: 10.1002/ejic.200700847
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Flexible Multidentate Ligands for Crystal Engineering: Syntheses, Structures, and Properties of CuII, MnII Complexes with N‐[(3‐Carboxyphenyl)sulfonyl]glycine and N,N′‐(1,3‐Phenylenedisulfonyl)bis(glycine)

Abstract: One novel N‐[(3‐carboxyphenyl)sulfonyl]glycine (H3L1) ligand (1) was prepared in high yield, and its structure was determined by single‐crystal X‐ray diffraction. Reaction of H3L1 with Mn(ClO4)2·6H2O at different pH values gave two new dinuclear complexes: [Mn2(HL1)2(phen)4]·16H2O (2) and [Mn2L1(phen)4(H2O)]ClO4·3H2O (3) (phen = 1,10‐phenanthroline). Additionally, two copper(II) complexes, [K2Cu(L2)2(H2O)2]n (4) and [CuL2(H2O)]2·2H2O (5), involving another novel ligand, N,N′‐(1,3‐phenylenedisulfonyl)bis(glycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Interest in rational design and synthesis of polynuclear coordination compounds with predictable functionalities, such as bioactivity [1][2][3][4][5], catalytic ability [6][7][8] and magnetic interactions [9][10][11][12][13][14] has increased tremendously in the recent years. Particularly, the design of bridging ligands that display several different coordination modes has been the focus for a great deal of researches, since the discovery that certain paramagnetic polynuclear metal complexes exhibit single-molecular-magnetic properties [15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…Interest in rational design and synthesis of polynuclear coordination compounds with predictable functionalities, such as bioactivity [1][2][3][4][5], catalytic ability [6][7][8] and magnetic interactions [9][10][11][12][13][14] has increased tremendously in the recent years. Particularly, the design of bridging ligands that display several different coordination modes has been the focus for a great deal of researches, since the discovery that certain paramagnetic polynuclear metal complexes exhibit single-molecular-magnetic properties [15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…A closer view of the (H 2 O) 12 cluster illustrates that each water monomer, except for O8, acts as both a hydrogen-bonding donor and accep-tor. In the supramolecular (H 2 O) 12 morphology, the OÁ Á ÁO distances range from 2.592 to 3.079 Å, resulting in an average OÁ Á ÁO distance of 2.800 Å, which is very close to those observed in liquid water (2.80 Å) [18] and comparable to the corresponding value in the ice phase (2.77-2.84 Å) [19]. However, the OÁ Á ÁOÁ Á ÁO angles vary widely (ca.…”
Section: Resultsmentioning
confidence: 61%
“…[1][2][3][4][5][6] It has been found that Nsulfonyl-amino acids can reproduce the coordination behavior of peptide and their selectivity towards metal ions. [7][8][9][10] The substitution of an Ar-SO − 2 group on amine nitrogen of amino acids such as glycine and L-glutamic increases the coordination donors to three types of O, N donors from carboxyl, sulfoxyl, and amine, respectively, which is able to result in different coordination modes.…”
Section: Introductionmentioning
confidence: 98%